PENERAPAN NILAI-NILAI AKHLAK ISLAMI DALAM KEPEMIMPINAN PENDIDIKAN: STUDI KASUS DI SMA IT BAITUSSALAM PRAMBANAN - Habiburrahman Habiburrahman; Rijal Khoirul Anam; Sabaruddin Sabaruddin (MPI STAI Sangatta Kutai Timur, 2025)
This study aims to understand the implementation of Islamic moral values in educational leadership at SMA IT Baitussalam Prambanan. Employing a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The data were analyzed thematically using data condensation, display, and conclusion drawing, and validated through source triangulation. The findings reveal that the principal successfully integrated Islamic values—Siddiq (truthfulness), Tabligh (communication), Amanah (trustworthiness), and Fathanah (wisdom)—into all aspects of leadership. Habituation programs, such as congregational prayers and Islamic etiquette, effectively shaped student character and strengthened relationships among school stakeholders. Furthermore, an adaptive and collaborative leadership style fostered innovation and created a harmonious working environment. Despite challenges such as initial resistance and the influence of global culture, approaches based on empathy and effective communication proved successful in overcoming these barriers. This study highlights the importance of Islamic leadership as both an ethical foundation and a practical framework for managing educational institutions in the modern era.